Penanaman Modal Asing dalam Mewujudkan Kesejahteraan Rakyat melalui Program Making Indonesia 4.0 - Agustini, Shenti; Tan, Winsherly; Aguslina, Aguslina (JUNCTO: Jurnal Ilmiah Hukum, 2024)
The Industrial Revolution 4.0, which was initially introduced in Germany, have brought significant implications for the industrial sector in various countries. One of them is Indonesia, as a country that felt the implications and experienced both positive and negative consequences from this change. To anticipate transformation in the industrial sector, the Ministry of Industry initiated the launch of the Making Indonesia 4.0 program. This program aims to accelerate the adaptation of the industrial ecosystem in Indonesia to the industrial era 4.0 which prioritizes the use of information technology in production and management processes. Apart from that, the Making Indonesia 4.0 program is also directed at intensifying the welfare of the Indonesian people through increasing the Gross Domestic Product (GDP) and creating new employment. The study method used is the normative juridical approach, this approach is a scientific study procedure that aims to find the truth based on legal scientific logic from a normative perspective. This study aims to investigate the implications of foreign investment and related regulations for example, Law No. 11 of 2020 concerning Job Creation and Law No. 25 of 2007 concerning Capital Investment, in increasing community welfare through the implementation of the Making Indonesia 4.0 program. The results of this research prove that there is a close relationship between the growth in the amount of foreign investment and the increase in social welfare, especially in terms of the increment in the number of employment opportunities.